Natural grassland remnants in dynamic agricultural landscapes: identifying drivers of fragmentation - C. Ríos; F. Lezama; G. Rama; G. Baldi; S. Baeza (Perspectives in Ecology and Conservation, 2022)
Grasslands have been subject to contraction and fragmentation processes worldwide, mainly due to their transformation into commercial tree plantations and agricultural lands. Identifying the remaining grasslands areas and the drivers of its fragmentation constitute an important step towards their appreciation, conservation and sustainability monitoring. The Eastern Plains of Uruguay constitute a region of recognized national and international conservation importance, but rice cultivation has spread extensively over the last 60 years, resulting in a strong transformation of its natural biomes. Our objectives were to map natural grasslands remnants in this complex landscape characterized by a high presence of different post-agricultural stages of vegetation; to quantify grassland fragmentation and its spatial variability in the landscape; and to identify the main drivers of the fragmentation process. We intersected a current supervised classification of the Eastern Plains of Uruguay (743,600 ha) with a mask of croplands from the previous ten years to discriminate grasslands remnants. We quantified the landscape fragmentation and described the relative contribution of different biophysical and anthropogenic factors in grasslands spatial configuration. Our results showed that natural grassland currently occupies only 21% of the Eastern Plains surface and it is in an advanced stage of fragmentation, comparable to that of the most historically transformed regions of the Rio de la Plata Grasslands. A few variables that determine the expansion of agriculture (large cadastral parcels size, high road network density and low topographical variation) drive the fragmentation process, relegating grassland to places with unfavorable characteristics for the development of rice cultivation.